Zastosowanie wybranych estymatorów modelu regresji logistycznej w credit scoringu - Michalski, Piotr (Application of Selected Estimators of Logistic Regression Models in Credit Scoring, 2008)
The article examines the application opportunities of different logistic regression models in a credit scoring supervised classification problem. The paper covers linear and generalized additive logistic regression model, as well as a classification trees boosting method - Real AdaBoost. The empirical study of two real credit datasets is given.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 27, s. 36-50